2015
DOI: 10.1063/1.4928339
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent electrical transport characteristics of BaTiO3 modified lithium borate glasses

Abstract: The glass samples with composition (70B2O3-29Li2O-1Dy2O3)-xBT; x = 0, 10 and 20 weight percent, have been prepared by conventional melt quench technique. The dielectric measurements as a function of temperature have been carried out on these samples in the frequency range 1 Hz-10 MHz. The dielectric relaxation characteristics of these samples have been studied by analyzing dielectric spectroscopy, dielectric loss, electric modulus formulation and electrical conductivity spectroscopy. It is found that the diele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The low‐frequency region of M ″ peak determines the range in which the charge carriers are confined to potential wells and mobile for very short distances, which is where ac conductivity dominates. Hence, the frequency range where the relaxation peak occurs suggests the transition region from long‐range to short‐range mobility of charge carriers . This relaxation peak moves toward higher frequency with increasing temperature.…”
Section: Dielectric Modulusmentioning
confidence: 95%
“…The low‐frequency region of M ″ peak determines the range in which the charge carriers are confined to potential wells and mobile for very short distances, which is where ac conductivity dominates. Hence, the frequency range where the relaxation peak occurs suggests the transition region from long‐range to short‐range mobility of charge carriers . This relaxation peak moves toward higher frequency with increasing temperature.…”
Section: Dielectric Modulusmentioning
confidence: 95%
“…• In the correlated barrier hopping (CBH) model [42], a temperature-dependence of exponent (s) and decreases with the increase in temperature.…”
Section: Ac Conductivitymentioning
confidence: 99%
“…6. The conductivity mechanism for any material could be explained by the temperature-dependent behavior of (s) [41][42]. In other words, the relation between the temperature and the value of (s) gives a good knowledge about the charge transport mechanism in dielectric substances.…”
Section: Ac Conductivitymentioning
confidence: 99%
“…Deviations from the power low correspond to n increasing with frequency and here, as in majority of disordered solids, n value in the high frequency region is between 0.5 and 1.0. Literature data [31][32][33] have shown that the conductivity mechanism in any material could be understood from the temperature dependent behaviour of n. To comprehend the electrical conduction mechanism in the materials, different models have been proposed (regarding frequency and temperature dependence of the exponent n). If the exponent n depends on the frequency but it is temperature independent, the quantum mechanical tunnelling (QMT) model can be proposed where the conductivity is believed to be due to the phonon-assisted tunnelling between defect states.…”
Section: Impedance Analysismentioning
confidence: 99%
“…In this model, tunnelling of polarons is the dominant mechanism; the large polaron wells at two sites overlap and reduce the polaron-hopping energy. Finally, if the exponent n decreases with temperature, the correlated barrier hopping (CBH) model can be suggested, according to which the charge transport occurs between localized states due to the hopping over the potential barriers [32].…”
Section: Impedance Analysismentioning
confidence: 99%